34‐3: High Contrast Research of 4K ADS TV Technology. Issue 1 (28th June 2022) - Hu, Hongling; Wang, Kai; Jiang, Liangliang; Zhang, Heng; Li, Yajun; Li, Xiaobin; Huang, Yinhu; Lim, Byung-cheon; Wang, Zhangtao; Shao, Xibin
Abstract : The Contrast of 4K ADS products was improved from 1500:1 to 3000:1 by material and process optimization, which includes the application of Ultra‐low Scattering Negative Liquid Crystal, Higher polarization polarizer, Thicker polyimide film and appropriately widened Black Matrix. The realization of Contrast 3000 records the highest in ADS Mode, greatly shortens the gap with VA products and also shows good applicability in high end LCD products.